Donald Trump’s grammar: How to trivialize facts on coronavirus - Fanani, Achmad (Englisia: Journal of Language, Education, and Humanities, 2022)
This current research reveals how President Trump grammatically constructed his clauses to trivialize the coronavirus (COVID-19). This research uses a discourse analysis approach with a qualitative design. The research data are President Trump’s trivializing clauses (192 main clauses) taken from his speeches, press interviews, remarks, and tweets from January 2020 to June 2020. Hallidayan SFL and Straker’s technique of trivialization are used as the basis of analysis. The result shows that most of the trivializing clauses are declarative while the others are interrogative and imperative. It is also identified that the declarative mood (statements of opinion and fact) reflects the techniques of sneaking through, trivializing the target, and discounting the target. The interrogative mood (rhetorical questions) demonstrates the technique of discounting the target. In addition, the imperative mood (directives) reflects the technique of sneaking through. Finally, the result also shows that oversimplification, severity decrease, and exaggeration characterize President Trump’s trivializing clauses.